2013
DOI: 10.4103/0974-1208.117177
|View full text |Cite
|
Sign up to set email alerts
|

Cytogenetic evaluation of patients with clinical spectrum of Turner syndrome

Abstract: AIM:The objective of this study was to correlate the genotype, of female patients, withshort stature and primary amenorrhea.MATERIALS AND METHODS:One hundred and forty-six subjects were recruited during 2005-2012. Microscopic and automated karyotyping analyses were done by using chromosomes isolated from the lymphocytes using Giemsa banding (GTG) to identify chromosome abnormalities.RESULTS:A total of 146 clinically suspected Turner syndrome (TS) subjects were recruited for the study, of which, 61 patients wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
10
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 21 publications
(21 reference statements)
1
10
0
1
Order By: Relevance
“…A wide spectrum of turner phenotypes are observed in 45, X/46, XX mosaic cases; the eventual phenotype varies from normal female to severe TS stigmata depending very much on the relative proportions of the two cell lines. 76 Generally, the presence of stigmata and severity of associated comorbidities in mosaic 45, X/46, XX individuals are milder than in 45, X individuals. Spontaneous menarche and development of secondary sex characters occurred higher frequencies in compared to classical 45, X individuals.…”
Section: Pure Turner Cases (45 X)mentioning
confidence: 99%
“…A wide spectrum of turner phenotypes are observed in 45, X/46, XX mosaic cases; the eventual phenotype varies from normal female to severe TS stigmata depending very much on the relative proportions of the two cell lines. 76 Generally, the presence of stigmata and severity of associated comorbidities in mosaic 45, X/46, XX individuals are milder than in 45, X individuals. Spontaneous menarche and development of secondary sex characters occurred higher frequencies in compared to classical 45, X individuals.…”
Section: Pure Turner Cases (45 X)mentioning
confidence: 99%
“…Turner syndrome (TS) is the most common chromosomal aneuploidy that affects 1 in every 2,000 girls, and is characterized by short stature and gonadal dysgenesis in females who lack all or part of one X chromosome 1) . Approximately 50% of patients with TS have complete loss of one X chromosome, whereas the rest of patients with TS display mosaicism or structural abnormalities of the X chromosome, for example, 46, X, i(Xq), 46, X, del(X), 46, X, r(X), etc.…”
Section: Introductionmentioning
confidence: 99%
“…Previous animal studies have shown that AR exon 1 deleted females with loss of AR protein exhibited increased atresia, which is positively correlated with an early decline in follicle number leading to accelerated ovarian failure [Shiina et al 2006]. Furthermore, it is known that a partial deletion of the long arm X chromosome, with the critical region Xq13-q26, causes significant ovarian insufficiency and gonodal dysgenesis [Moka et al 2013]. This concurs with the observations of the patient presented here with the absence of ovaries detected by the USG examination.…”
Section: Discussionmentioning
confidence: 99%